The risk associated with iron deficiency anemia for simple febrile seizures in children: A case–control study - Tripathy, Debajyoti; Tomar, Rampal Singh; Gupta, Ashish Kumar; Ghuliani, Ranjit (Indian Journal of Child Health, 2020)
Background: Studies have postulated iron deficiency state to be a risk factor for febrile convulsions as it changes the threshold of neurons excitation which may lower the threshold for seizures in children. However, many other studies have reported a protective role for febrile convulsions by increasing the neuronal threshold. Objective: The objective of the study was to evaluate the association of iron deficiency anemia (IDA) as a risk factor for the occurrence of simple febrile seizures (FS) in children. Material and Methods: A case-control study was conducted in a tertiary teaching hospital from September 2015 to February 2017. A total of 240 cases with fever and simple FS were enrolled according to the inclusion and exclusion criteria. Another 100 cases of children without seizure but with short duration of fever were enrolled as controls. Blood samples were then taken for assessing the hematological indices of these patients. The results were statistically analyzed. Results: Incidence of IDA was found to be more in children with simple FS than controls but was not statistically significant (p=0.35). Furthermore, no association was found with other hematological indices with FS occurrence. Conclusion: We could not find any association of IDA as a risk factor for a simple FS.